SEQUENCE ANALYSIS OF Streptococcus agalactiae, A PATHOGEN CAUSING STREPTOCOCCOSIS IN TILAPIA (Oreochromis niloticus) - Angela Mariana Lusiastuti; Taukhid Taukhid; Eni Kusrini; Wartono Hadie (Indonesian Aquaculture Journal, 2009)
Pathogen identification based on biochemical properties can barely differentiate Streptococcus iniae and S. agalactiae. Beside that, this technique is also limited by the length of time required to complete the assays. Therefore, rapid diagnosis is necessary to initiate prompt therapeutic and prophylactic measures in order to limit any potential economic losses caused by such pathogens. The aim of the present study was to identify Streptococcosis species using amplification of S. agalactiae DNA sequence with species-specific primer Sdi 61 AGGAAACCTGCCATTTGCG and Sdi 252 CAATCTATTTCTAGATCGTGG and perform phylogenetic analysis based on DNA nucleotide sequence data. The sequencing of PCR products was performed at BPPT Puspiptek Serpong by using the respective PCR primers, Big Dye Terminator Chemistry and AmpliTaq-FS DNA polymerase. The sequencing reactions were run on the ABI Prism version 3103 – Avant Genetic Analyzer (USA) and the result was read by Sequence Navigator program (Applied Biosystem). Alignment multiple analysis was done based on the data from Genebank with BLASTN (http://blast.ncbi.nlm.nih.gov/blast.cgi) on the nucleotide level. Neighbor-joining phylogenetic trees were generated with Genetyx programme version 7 with UPGMA and MEGA software version 4.0. The result revealed that the isolates from brain, eye, and kidney of diseased Tilapia were infected by S. agalactiae and it has 99% similarity with Genebank. It has close relationship with S. agalactiae at genebank with UPGMA method. These isolates showed high variation in the first sequence which is similar to S. iniae. The information of S. agalactiae genomes suggests that gene acquisition, duplication, and reassortment have played an important role in genetic diversity and evolution of S. agalactiae. Screening of breeder fish stocks with the developed PCR methodology, followed by elimination of infected stocks, would provide an efficient strategy to control fish infected by streptococcosis.